ANALISIS PERILAKU PETANI KOPI SERTIFIKASI DALAM MENGELOLA RISIKO LINGKUNGAN DI KABUPATEN TANGGAMUS - Rizka Esty Wulandari; Bustanul Arifin; Zainal Abidin (Jurnal Ilmu Ilmu Agribisnis: Journal of Agribusiness Science, 2019)
This research aims to analyze coffee farming income in Tanggamus District, behavior of coffee farmers in managing environmental risk, and factors that influence behavior of coffee farmers in managing environmental risk. This research was conducted in Sinar Sekampung Village, Air Naningan Sub-District and Gunung Meraksa Village, Pulau Panggung Sub-District in August 2017. The sample in this study involved 44 certification coffee farmers chosen using cluster random sampling method and 24 noncertification coffee farmers chosen using census method. The difference of coffee farming income is analyzed using Independent Sample t-test, while the difference of behavior is analyzed using Mann Whitney Test and the factors is analyzed using binary logistic regression. The results showed that there was no difference in coffee farmers income between certification farmers and noncertification coffee farmers. Sixty-three percents of certification coffee farmers were risk takers and 87,50% of nonacertification coffee farmers were risk neutral. Factors that influence behavior of coffee farmers in managing environmental risk were land area, coffee farming income, and participation of farmers in 4C certification program.Key words: coffee certification, environmental risk, coffee farming income